$1!0$!:R!Q<s - Anonymous (Salt Lake City, UT : Project Gutenberg, 2004)
"$1!0$!:R!Q<(B" by Anonymous is a Chinese classic text probably written in the 13th century. This foundational educational work teaches children through memorable three-character verses, introducing common characters, grammar, Chinese history, and Confucian values like filial piety. For centuries, it served as the primary literacy text for young students across China, enabling them to recognize thousands of characters through rhythmic recitation. The opening verses declare Confucianism's core belief: that human nature is inherently good, though habits shape us differently. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Three_Character_Classic
Release date is 2004-05-01
Keywords: Chinese language -- Readers